Strategy For Decision-Making On Old Age Security (Jht) Benefit Claims At Bpjs Ketenagakerjaan - Lya Utami, Mei; Zulbainarni, Nimmi; Taryana, Asep (Asian Journal of Social and Humanities, 2025)
The phenomenon of high claims for Old Age Security (JHT) before retirement age poses a challenge to the sustainability of social security programs in Indonesia. This study aims to analyze the behavioral and policy factors that influence JHT claim decisions and formulate strategies for optimizing the claim mechanism. The research method was conducted through Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis of 232 respondents who were JHT participants who had made claims, as well as the Analytic Hierarchy Process (AHP) method involving 15 experts in the fields of social security, public policy, and financial behavior. The results show that the behavioral factors of loss aversion, present bias, and mental accounting have a significant effect on JHT claim decisions, supported by government regulations that reinforce the tendency for early claims. Meanwhile, the AHP results placed Effectiveness as the main criterion in determining strategy and produced optimal optimization strategy priorities in the form of increasing financial literacy and socializing mindset changes based on behavioral economics, followed by reformulating JHT disbursement policies and other supporting strategies. This study confirms that JHT claim behavior is influenced by psychological biases and prevailing policies, so optimization efforts need to be directed towards educational approaches, policy reforms, and sustainable service innovations.